A efitividade do processo executivo de acordo com a certeza, liquidez e exigibilidade do título, judicial ou extrajudicial - Caldas, Renato Vinícius (2015)
This work is a study of the execution process, whether judicial or extrajudicial title. When the claimants have a credit, this wants to see you satisfied, that is, you want the lender to fulfill its obligation, if not spontaneously, will be through the Judiciary machine by means of coercive powers imposed by law . For this to happen the lender must necessarily be fitted with an enforcement order, which may be legal, ie have their right recognized by the judiciary through a stock of knowledge, or extrajudicial, that is, the law regulates the document has enforceable, which makes unnecessary, thus their submission to a knowledge of action. And it is exactly the concentration of this study, which will address how this title shall be implemented by analyzing its liquidity, certainty and enforceability, and the consequent realization of the executive process for such securities, in accordance with the procedures established by law